(untitled) (Global Journal of Human-Social Science, 2013)
This study is presenting an empirical justification for the inclusion of private sector participation in municipal solid waste management It is derived from a study of waste management in metropolitan Lagos Primary data were obtained through interviews and ten questionnaires with the various stakeholders and secondary data were collated from the archives of relevant agencies especially Lagos Waste Management Authority LAWMA websites Digital libraries and earlier studies The study reveals that the private sector which comprises of the highway managers and the private sector participant PSP collected more than 70 of the waste volume even in the experimental stage This is a pointer to the potential of this sector as a strong ally and a more efficient one at that